LINGUOSTYLISTIC MEANS OF VERBALIZING INDIVIDUAL RESILIENCE IN YULIA PAIEVSKA’S TEXTS «NAZHYVO» («LIVE») - Kukharuk , Khrystyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article presents a study of the linguostylistic representation of individual resilience as a cognitive and linguistic strategy for coping with psychotraumatic experiences. The relevance of this research stems from the lack of linguistic descriptions of the Ukrainian language's stylistic means that explicate the vitality and resilience of individuals who survived combat and military captivity during the Russian-Ukrainian War. The object of the study is the collection of texts by Yulia Paievska titled «Nazhyvo» («Live»), representing Ukrainian military and volunteer discourse. The subject encompasses linguostylistic means (lexical, morphological, and syntactic) and linguocognitive mechanisms (metaphorization, recategorization, and axiological marking). The aim is to identify and typologize the linguistic and stylistic means of verbalizing resilience, including their visualization and interpretation. To achieve this, a typological method (to classify explicants), content analysis (to determine specificity and frequency), visualization (for infographics), and descriptive methods were employed. The findings provide a typology of linguostylistic means of verbalizing individual resilience across language levels. At the grammatical level, there is a dominance of active verbs («we hold on»), denoting agency and the rejection of the victim role, alongside the category of futurality («we will win») as a projection into the future. At the lexico-semantic level, the study highlights the semantic field of stability, the terminologization of emotions (including professional slang), and the defense mechanism of irony (black humor, euphemisms). At the stylistic level, metaphors of resistance and firmness («metal», «concrete»), the metaphor of «war as work», and parcellation (syntactic laconism) are identified. Within Yulia Paievska's idiolect, specific markers of resilience are revealed: axiological accents («honor», «will») that perform a linguocognitive reframing function, and the «paradox of calm» – a narrative construction that balances the horrors of war with linguistic «grounding». The study concludes that the linguostylistic verbalization of resilience is a systemic tool for overcoming trauma at the cognitive level. Content analysis reveals three main vectors of resilience in the «Nazhyvo» («Live») texts: metaphorical transitivity, temporal correlation, and stylistic opposition. It is argued that «calmness» in this context is not an absence of emotion, but a higher level of emotional organization through language.